Validation of the Family Educational and Learning Capitals Questionnaire: An Australian Perspective. (December 2017) - Phillipson, Shane N.; Phillipson, Sivanes; Francis, Mariko A.
There is a growing recognition that parents play an important role in the academic achievement of their children. This role includes both the interactions they have with their children and the management of resources that can contribute to their children's achievement. To better understand parents' roles, it is important to understand their perceptions regarding the availability of these resources. This article reports the validation of the Family Educational and Learning Capitals Questionnaire (FELCQ), an instrument that measures parents' perceptions of educational and learning resources. Based on the Actiotope Model of Giftedness, the FELCQ consists of five educational and five learning capitals plus parental aspirations for their children's achievement. The responses of 1, 917 Australian parents to the 53-item FELCQ were Rasch analyzed and the Rasch person estimates were utilized in a confirmatory factor analysis to confirm the FELCQ as a valid measure of parents' perceptions of the capitals. The results showed that the FELCQ reflects the underlying theoretical factor structure of the Actiotope Model, including the extension of the model to include parental aspirations as an educational capital for parents in relation to their children's education. The implications and future use of the FELCQ are discussed.